The voltage effect: How to make good ideas great and great ideas scale - List, John A. (UK Penguin business, 2022)
The definitive guide to the science of scalability- how to make good ideas great, and great ideas scale. Why do some ideas make it big while others fail to take off? According to award-winning behavioural economist John List, the answer comes down to a single question- Can the idea scale? Countless enterprises fall apart the moment they scale; their positive results fizzle, they lose valuable time and money, and the great electric charge of potential that drove them early on disappears. In short, they suffer a voltage drop.
Keywords: Success in business; Strategic planning; Business enterprises growth